Incidence and Predictors of Calf Morbidity and Mortality From Birth to 6-Months of Age in Dairy Farms of Northwestern Ethiopia - Alemu, Yeshwas F.; Jemberu, Wudu T.; Mekuriaw, Zeleke; Abdi, Reta Duguma (Frontiers in Veterinary Science, 2022)
Ethiopia has planned to expand its crossbred dairy sector but little is known about calf health. This longitudinal study aimed to quantify the incidence and identify predictors of calf morbidity and mortality from birth to six-months of age in urban and peri urban dairy farms of Northwest Ethiopia. A total of 439 calves aged below six months from 174 dairy farms were included in the study. We evaluated the effect of 35 potential risk factors on calf morbidity and mortality in the area. Kaplan-Meier survival analysis was used to summarize survival probability. Moreover, the Cox proportional hazard regression model with shared frailty to account for unmeasured herd specific heterogeneity was used to identify and quantify factors associated with time to morbidity and mortality. Among 439 calves enrolled for six months of follow up period, a total of 141 morbidity and 54 mortality events were recorded. This gives an overall morbidity and mortality incidence rates of 64 per 100-calf six-months at risk (risk rate of 47.3%) and 19 per 100-calf six-months at risk (risk rate of 17.9%), respectively. Diarrhea was the most frequent calf health problem with risk rate of 25.2%. It was the cause of death for 33.3% of all the 54 calf deaths. Next to diarrhea, pneumonia ranked second with risk rate of 8.6% and responsible for death of 12.9% of all the 54 calf deaths. Of 35 potential risk factors, calf age, vigor status at birth, calf breed, colostrum ingestion and herd size were significant (p<0.05) predictors of calf morbidity and mortality. The Cox-shred frailty model revealed that the herd frailty component had no significant effect on hazard estimates of the covariates of all-cause morbidity and mortality. This implies that the studied dairy herds were homogeneous in the distribution of unmeasured random effects. In conclusion, the magnitude of calf morbidity and mortality was higher and above economically tolerable level in this study. Therefore, interventions directed at the identified potential risk factors have the potential to reduce morbidity and mortality in the study area.